A gene cloning system for the siomycin producer Streptomyces sioyaensis NRRL-B5408 - Myronovskyy, M; Ostash, B; Ostash, I; Fedorenko, V (Folia microbiologica, 2009)
Streptomyces sioyaensis NRRL-B5408 produces a siomycin complex (a group of thiopeptide antibiotics structurally related to thiostrepton). Development of genetic tools for the detection of siomycin production and DNA transfer into this strain is described. The existing tipA-based reporter system for determination of siomycin production was modified to achieve its stable integration into actinomycete genomes. Various replicative plasmids (pKC1139, pKC1218E, pSOK101) as well as actinophage phi C31- and VWB-based vectors pSET152 and pSOK804, respectively, were conjugally transferred from E. coli into the siomycin producer at a frequency ranging from 3.7 x 10(-9) to 1.1 x 10(-5). The transconjugants did not differ from wild type in their ability to produce siomycin. There is one attB site for each integrative plasmid. The utility of temperature sensitive replicon of pKC1139 for insertional gene inactivation in S. sioyaensis has been validated by disruption of putative nonribosomal peptide synthetase gene.
Keywords: Plasmids; Genetic Vectors; plazmidy; Cloning, Molecular; Genes, Reporter; antibakteriální látky; Financing, Organized; financování organizované; peptidy; Conjugation, Genetic; konjugace genetická; reportérové geny; Anti-Bacterial Agents; Peptides; klonování DNA; genetické vektory; technika přenosu genů; Streptomyces; Gene Transfer Techniques